Drip Irrigation Technology Performance on Rice Cultivation - Priatna Sasmita; Nurwulan Agustiani; Swisci Margaret; Shinta Dewi Ardhiyanti; Suprihanto Suprihanto; Yudhistira Nugraha; Suhartini Suhartini (The University of Lampung, 2022)
This study aims to determine the performance of drip irrigation technology as compared to conventional farmer’s practice on rice growth and yield, grain quality, and water consumption. The research was carried out at the Sukamandi Experimental Station, Subang, West Java in July - October 2019. The test was arranged by a nested randomized block design with 5 replications. The main plot was water management with 2 levels: (1) Drip Irrigation Technology (DIT) and (2) Conventional Farmer’s Practice (CFP) (flooded condition) as a comparation. Subplot was varieties with 4 levels: two hybrid rice (1) Hipa 8 and (2) Hipa 18, upland rice (3) Inpago 11, and irrigated inbred rice (4) Inpari 42. The result showed that yield of DIT not significantly different to CFP with higher number of tillers per m2. However, it was lower for plant height, tillering ability, grain filling, 1000 grains weight, transpiration rate, assimilation rate and stomatal conductance. For grain quality determination, DIT gave an increase in the average of grain density and impurities, but decreased in the average percentage of chalky and immature grains. In Hipa 18, DIT was able to produce a higher percentage of head rice. DIT only consumed 3864 m3/ha/season water irrigation compared with average water consumption in Sukamandi Field Station which range of 7460-8740 m3/ha/season.Keywords: Drip irrigation, Rice, Water, Yield, Grain quality